Mapping SDG Synergies: Digitalization, Sustainable Development Goals, and Evolving Patient Expectations in Modern Healthcare - Kesavan Sreekantan Nair (Open Access Public Health and Health Administration Review, 2026)
The contemporary global healthcare landscape is undergoing an unprecedented paradigm shift driven by rapid technological innovation and shifting population demographics. As health systems worldwide strive to fulfill the United Nations’ Sustainable Development Goals (SDGs)—most notably SDG 3, which aims to ensure healthy lives and promote well-being for all at all ages—the integration of digital tools has transitioned from an optional enhancement to a core structural necessity. Modern healthcare delivery is no longer defined solely by clinical interactions within physical facilities; rather, it operates at a dynamic intersection where artificial intelligence (AI), mobile health applications, electronic health record (EHR) ecosystems, and remote patient monitoring converge. This digital transformation brings profound opportunities alongside critical vulnerabilities. While digital tools improve healthcare accessibility and structural efficiency, they also alter patient behaviors, driving new expectations for convenience, transparency, and personal agency. For health researchers, clinicians, and policymakers, understanding the interplay among the SDGs, the digitalization of health systems, and shifting patient expectations is vital for designing equitable, sustainable, and high-quality care frameworks. By focusing scholarship on these intersections, the scientific community can ensure that digital transformations strengthen equitable, sustainable, and patient-centered health systems worldwide.